Avaliação da eficiência técnica de sistemas agrícolas cultivadas com uso da palha de carnaúba (Copernicia prunifera [Miller] H.E Moore) no semi-árido piauiense - Macêdo, Francisca Nilcélia Alves (2007)
An important source of organic matter that can be supplied to the soil is the mulching, like carnauba straw, per example. The tree of carnauba is an abundant palm tree in the semi-arid region of Piauí, where it is used to obtain wax. The straw obtained of this extraction can be used in the agriculture as mulching, bringing countless benefits to the soil. Thus, the purpose of the present work was to evaluate the technical efficiency of agricultural systems cultivated with use of carnauba straw in semi-arid of Piauí. Socioeconomics questionnaires were applied with 17 families of rural producers in Aroeiras do Itaim-PI, some of the rural producers used carnauba straw in the systems of annual cultivations (bean, corn and rice) and others did not use carnauba straw in the systems of annual cultivations. The analysis of the technical efficiency of the family units was made through the application of Data Envelopment Analysis (DEA). It was verified that the systems cultivated with use of carnauba straw improved the economic performances and obtained larger technical efficiency.